The Analysis of Code-Switching on Comfort in Expressing True Meanings in TikTok Influencers Content - Mahmud, Murni; Burhamzah, Muftihaturrahmah; Zachira, Amirah Maraya; Efendi, Faturrahman (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to address this gap by examining the use of code-switching in TikTok influencer content and its impact on the convenience of conveying true meaning. Code- switching, which is prevalent in bilingual and multilingual communication, has attracted much attention in various contexts. The emergence of social media platforms has changed the way individuals communicate and convey their identities. Through a qualitative approach, this study explores an in-depth understanding of discourse analysis and identifies code-switching that appears in TikTok content. It is evident that this linguistic strategy serves as a powerful tool to convey true meaning with ease and comprehensibility. In addition, this research will provide insight into the linguistic and cultural competencies required to use code-switching proficiently in online communication. Keywords: Tiktok influencer, Code-swicthing, social media, TikTok content, and True meanings